STRATEGIC MARKETING IN CRISIS (COVID-19 PANDEMIC): A STUDY AT PRIMEBIZ HOTEL SURABAYA - Mohammad Jamil Rizwan; Gancar Candra Premananto (Jurnal Bisnis dan Keuangan, 2022)
COVID-19 pandemic has disrupted the global economy including the hotel industry locally and internationally. It has spread to practically every country in the world. While the survival of the hotel industry was at its stake, there was a need for research to know management's response to this crisis and opted strategies for survival. The purpose of this research is to design a marketing strategy at PrimeBiz Hotel Surabaya that deals with COVID-19. This research was conducted using a qualitative approach based on case studies. This study uses triangulation methods to validate and view from various perspectives. The data collection procedure used in this study was in-depth interviews. The findings of this study indicate that the economic crisis brought on by the coronavirus had an effect on the hotel in Indonesia. Overall, the key findings imply that the PrimeBiz hotel improved and adjusted its marketing mix in response to the issue. The Indonesian PrimeBiz hotel was required to alter its marketing mix as a result of the shift in consumer purchasing behavior, which was a significant factor. In order to prevent the virus from spreading, the Indonesian government and the Public Health Agency put in place measures like social exclusion, travel restrictions, and solid borders.